MODEL HEXAHELIX: IMPLEMENTASI PROGRAM PEMBERDAYAAN KELOMPOK WANITA TANI - Riza Purnama; Rakhmat Saleh; Tina Cahya Mulyatin; Nova Chalimah Girsang; Tofan Ibrahim (JURNAL DINAMIKA, 2025)
Empowering Women Farmers Groups (KWT) is an important strategy in strengthening food security, household economies, and inclusive rural development. However, the implementation of KWT empowerment programs often faces limitations in coordination, fragmentation of roles among actors, and weak program sustainability. This study aims to analyze the application of the Hexahelix Model as a collaborative approach in the implementation of KWT empowerment programs. The Hexahelix Model emphasizes the synergy of six key actors, namely the government, academics, business actors, communities, the media, and financial institutions, in an integrated policy ecosystem. Through a conceptualanalytical approach based on a review of the latest literature, this study shows that the Hexahelix Model is capable of strengthening the effectiveness of KWT empowerment programs through institutional capacity building, access to resources, local-based innovation, and expansion of marketing networks. Thus, the Hexahelix Model can be positioned as an adaptive and sustainable strategic framework in supporting women's empowerment in the agricultural sector.